EARLY PRECAMBRIAN MAFIC ROCKS OF THE FENNOSCANDIAN SHIELD AS A REFLECTION OF PLUME MAGMATISM: GEOCHEMICAL TYPES AND FORMATION STAGES - Arestova N.A.; Lobach-Zhuchenko S.B.; Chekulaev V.P.; Gus'kova E.G. (My University, 2003)
The analysis of radiometric ages of Early Precambrian basites of the Fennoscandian shield, from the most ancient ones, > 3.1 Ga, to 2.40 Ga, resolves five age groups of the basites. Each of these stages is shown to time span interval of 70-80 m.y. The early stages of the high-T mafic magmatism ( > 3.1 and 2.99-2.91 Ga) are confined to within the oldest core of continental crust in the Fennoscandian shield - the Vodlozero domain with crustal age of 3.2-3.4 Ga. The next stage of mafic magmatism (2.88-2.80 Ga) occurred within the Kola and western Karelian domains with crustal ages of 3.0 and 3.1 Ga and on the north of the younger, central Karelian domain. The last of the Archean stages of high-temperature mafic magmatism with ages of 2.72-2.66 Ga occurs in the north Karelian belts, in the Karelian part of the Belomorian area (the regions of Lake Notozero and the Tupaya Guba Bay of Lake Kovdozero) and possibly, in the western Karelian domain. This magmatism took place also immediately after the subduction processes at the boundary of the Karelian and Belomorian domains. The Early Proterozoic high-T mafic magmatism at 2.50-2.41 Ga was both the most areally extensive and continuos such episode in the Fennoscandian shield. Nearly all the researchers of the high-T basites of this stage attribute this magmatism to the ascent of a deep mantle super-plume. Paleomagnetic data provide further evidence that at 2.5-2.41 Ga a long-lived heat source occupied virtually the entire area of the present day Fennoscandian shield.
Keywords: EARLY PRECAMBRIAN; MAFIC ROCKS; PLUME MAGMATISM; FENNOSCANDIAN SHIELD; RADIOMETRIC AGES; Proterozoic; Archean; Precambrian::Proterozoic; Докембрий::Протерозой; Докембрий::Архей; Precambrian::Archean